The development of corticothalamic and corticotectal connections in the murine visual system - Grant, E (2014)
All peripheral sensory information is represented in the thalamus before being transmitted to the cortex, with the exception of olfaction. The thalamus projects to all areas of the neocortex and all neocortical areas project to the thalamus. I am interested in the development of three corticothalamic populations which are anatomically and functionally distinct; they project to different thalamic nuclei and generate different post-synaptic responses. Layer V fibres project exclusively to higher order thalamic nuclei. These projections drive thalamic neuron activity and mediate a trans-thalamic cortico-cortical relay. Layer VI and VIb fibres project to both first order and higher order thalamic nuclei. These projections modulate thalamic neuron activity and mediate feedback to the thalamus. Using three transgenic mouse lines I demonstrate that developing corticothalamic fibres target the specific groups of thalamic nuclei to which they project in adulthood. Rbp4-Cre::tdTomato labels layer V; Ntsr1-Cre::tdTomato labels layer VI; Golli-τ-eGFP labels layer VI and VIb. By P4 layer V fibres arborise densely in higher order nuclei but do not innervate the first order nuclei at any age. In contrast, at this age VI and VIb fibres densely innervate the first order ventral posterior-medial nucleus (VPM), as well as higher order nuclei. Layer VI and VIb fibres accumulate outside the dorsal Lateral Geniculate Nucleus (dLGN) from P2 before entering at P6. During this waiting period, retinal fibres transmit spontaneous waves of activity to the dLGN. To assess whether retinal input regulates corticothalamic circuit development I performed monocular enucleation. I demonstrate that after loss of retinal input, layer VI and VIb fibres enter the dLGN prematurely, by P2. Furthermore layer V fibres which target the retino-recipient superior colliculus also enter prematurely following enucleation. These results suggest there may be a retinal mechanism which regulates the timing of corticofugal ingrowth to joint retinal/cortical targets. The loss of retinal driver input to the dLGN also induces layer V driver fibres to aberrantly enter the first order dLGN. These results are the first to show cross-hierarchical rewiring after losing peripheral sensory input. The role of peripheral activity in the developing nervous system is underscored by activity dependent molecular mechanisms. I therefore performed a microarray gene expression experiment to systematically analyse molecular changes in the dLGN following enucleation. The expression of numerous genes is altered following enucleation including potassium channels Kcnk9 and Kcnn3, kinase pathway mediators, Shc3 and Dgkk, and immediate early genes BDNF, Egr1 and Egr2. The majority of genes regulated by enucleation are regulated in the opposite direction over development indicating that the loss of the retinal input delays maturation of the dLGN transcriptome. In this thesis I demonstrate that early corticothalamic development targets specific thalamic nuclei. Using the visual system as a model I demonstrate that retinal input regulates corticothalamic development and contributes to the transcriptome of thalamic nuclei.